The Forms of Loss and Stages of Grief in the Main Characters in the Film "Ketak Berhenti Disini": a Psychological Literary Approach - Ispa Ahwatul Muslimah; Rohanda Rohanda; Fadlil Yani Ainusyamsi (Gunung Djati Conference Series, 2025)
This study aims to describe the forms and types of loss and analyze the stages of grieving experienced by the main character in the film "Ketika Berhenti Di Sini" based on Kubler Ross' theory. The approach used in this research is literary psychology with qualitative descriptive method. Data sources in the research include dialog, stories, actions, and expressions of a main character related to the experience of loss and the stages of grieving. Data collection techniques include movie observation, recording emotional moments according to Kubler Ross' theory and the concept of loss. The findings of this study show that the main character named Dita experiences real losses such as the death of her father and her lover, as well as emotional losses related to a sense of security and self-stability. Both types of loss have a significant impact on Dita's psychological state. In dealing with the loss, Dita experiences five stages of grief, namely denial, anger, negotiation, depression, and acceptance. These stages can be seen from the changes in Dita's response, which began to escape to the virtual world until she finally accepted reality and continued her life. This research shows that film as a form of literary work can reflect the complexity of human emotional dynamics through the experience of loss and the grieving process experienced by its characters.